A confocal view of the calcifying odontogenic cyst: Report of two cases - Soumya Makarla; Madhura Bhat; Radhika Manoj Bavle; Paremala Kristam (Wolters Kluwer Medknow Publications, 2014)
The calcifying odontogenic cyst (COC) is a rare odontogenic lesion representing about 1% of all jaw cysts. There is a wide age range from 1 to 82 years with a first peak in the second decade and the second in the sixth/seventh decade. This lesion is characterized by the presence of "ghost" cells. The pathogenesis of the lesion is from the reduced enamel epithelium or the remnants of odontogenic epithelium. Here, we report two cases, both in 18-year-old male patients; previously diagnosed as dentigerous cyst and residual cyst respectively. But histologically, both the cases turned out to be COCs. Confocal laser scanning microscopy (CLSM) has become an invaluable tool for a wide range of investigations in the medical sciences for imaging thin optical sections of tissues. The COCs were evaluated using CLSM to analyze the properties of the cystic lining and the ghost cells.